2021
DOI: 10.1136/bmjopen-2020-046738
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, controlled, open label, multicentre clinical trial to explore safety and efficacy of hyperbaric oxygen for preventing ICU admission, morbidity and mortality in adult patients with COVID-19

Abstract: IntroductionCOVID-19 may cause severe pneumonitis and trigger a massive inflammatory response that requires ventilatory support. The intensive care unit (ICU)-mortality has been reported to be as high as 62%. Dexamethasone is the only of all anti-inflammatory drugs that have been tested to date that has shown a positive effect on mortality. We aim to explore if treatment with hyperbaric oxygen (HBO) is safe and effective for patients with severe COVID-19. Our hypothesis is that HBO can prevent ICU admission, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The side effects of the patients during the transfer may be related to the patient's condition, the excellent transfer equipment, the ability of the transfer personnel or the communication between the teams, the preparation before the transfer, and the monitoring during the transfer [ 8 ]. According to reports of adverse events during in-hospital transport, patients had different types of complications during in-hospital transport, of which 42.4% of the complications were related to hypoxia [ 9 ]. Some scholars reported that during the transfer of surgical patients to the ward, about 30% to 50% of patients developed hypoxemia after operation.…”
Section: Introductionmentioning
confidence: 99%
“…The side effects of the patients during the transfer may be related to the patient's condition, the excellent transfer equipment, the ability of the transfer personnel or the communication between the teams, the preparation before the transfer, and the monitoring during the transfer [ 8 ]. According to reports of adverse events during in-hospital transport, patients had different types of complications during in-hospital transport, of which 42.4% of the complications were related to hypoxia [ 9 ]. Some scholars reported that during the transfer of surgical patients to the ward, about 30% to 50% of patients developed hypoxemia after operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors of the present study believe that studies conducted on an older population can be the basis for the analysis of the positive effects of HBOT on pediatric patients following COVID-19 who are struggling with complications. Knowing the general effects of hyperbaric oxygen therapy including the alleviation of general inflammation by reducing the expression of TLR2 and TLR4 receptors and polarizing cytokine-secreting macrophages (and thus preventing acute respiratory failure), reducing fatigue and improving cognitive abilities, reducing tissue edema and improving tissue oxygenation, and antimicrobial activity [ 14 , 32 , 33 ], it can be expected that its effect will also be positive in the treatment of children with the pediatric inflammatory multisystem syndrome (PIMS, MIS-C) developed as a complication of COVID-19, and the treatment of other complications such as pediatric acute respiratory distress syndrome (PARDS). Both the occurrence of MIS-C and PARDS are likely to be initiated by the secretion of large amounts of pro-inflammatory cytokines and lead to multi-organ dysfunction [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBOT has previously been used as an adjunctive treatment for COVID-19, resulting in faster recovery in prospective trials, case series 13 and a randomised controlled trial (RCT), 14 with additional RCTs ongoing. 15 The rationale for treatment of COVID-19 with HBOT is the treatment’s well-established anti-inflammatory effects. 16 17 Furthermore, a small retrospective cohort study has shown promising results in alleviating symptoms of long COVID-19 in patients treated with HBOT.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) is administered by delivering 100% oxygen at raised pressure to patients in a hyperbaric chamber. HBOT has previously been used as an adjunctive treatment for COVID-19, resulting in faster recovery in prospective trials, case series13 and a randomised controlled trial (RCT),14 with additional RCTs ongoing 15. The rationale for treatment of COVID-19 with HBOT is the treatment’s well-established anti-inflammatory effects 16 17.…”
Section: Introduction/backgroundmentioning
confidence: 99%